In search of alternative frameworks the experience of Save the Children UK's NGO partners in early childhood care and development - Pura, Alexandra (Paperchase Print Services, 2001)
"This book brings together the experience of SC-UK and its partners in early childhood care and development (ECCD), taking into account the content and methodology developed, ways of working, and advocacy strategies in relation to the local context of each partner. It also attempts to assess and identify the different ECCD models used by the partners in the hope of defining the "alternative" framework. Lastly, it identifies good models of practice and draws up recommendations for further improving the work."--Executive summary.